Safety and efficacy of APSA PHYTAFEED® 20, 000 GR/L (6‐phytase) as a feed additive for chickens for fattening, chickens reared for laying and minor growing poultry species. (10th May 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: APSA PHYTAFEED ® 20, 000 GR/L is a preparation of 6‐phytase which is presented in solid and liquid forms. This additive is intended to be used as a zootechnical additive in chickens for fattening or reared for laying/breeding and minor poultry species for fattening or reared for laying/breeding. The 6‐phytase present in the additive is produced by a genetically modified strain of Komagataella phaffii . The production strain and its recombinant DNA were not detected in intermediate products used to produce the additive. The final products do not trigger a safety concern with regard to the genetic modification. Based on the results obtained in a tolerance study in chickens for fattening and the data from a subchronic oral toxicity study the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the additive is safe for chickens for fattening. This conclusion was extended to chickens reared for laying/breeding and extrapolated to all minor poultry species for fattening or reared for laying/breeding. The FEEDAP Panel concluded that the use of APSA PHYTAFEED ® 20, 000 GR/L as a feed additive gives rise to no concern for consumers. The additive, in either form, is not toxic by inhalation or irritant for skin or eyes and it is not a dermal sensitizer, but it is considered a potential respiratory sensitizer. The use of the product as a feed additive is of no concern for the environment. The FEEDAP Panel evaluated three efficacy trials in which the retention of the phosphorus was studied. The data showed that the additive has the potential to improve the retention of phosphorus in the diets in chickens for fattening at 250 U/kg feed. This conclusion was extended to chickens reared for laying/breeding and extrapolated to all minor poultry species for fattening or reared for laying/breeding.